Coffee Shop as Symbol Lifestyle of the Urban Community (Case Study on Customers of Coffee Shop in Makassar City) - Wahyu Hidayat; Hasbi (LEGAL BRIEF, 2022)
This study discusses visiting and spending time in coffee shops as a symbol of the lifestyle of urban communities in Makassar City. This can be seen from the people who often visit coffee shops which consist of various groups based on their backgrounds and professions. This study aims to identify various activities of urban communities on coffee shop customers among marketing, students, and online motorcycle taxis so that they often spend their time in coffee shops. This research was conducted in three coffee shops in Makassar using a qualitative approach in the form of descriptive qualitative with a case study basis, by interviewing 9 informants who were referred to as customers based on the intensity of their visits and 3 coffee shop managers. Data were collected through observation, in-depth interviews, and recommendations. The results of this study indicate that various customer activities in taking their time to coffee shops in Makassar City which started as a place to rest and relieve drowsiness, now visiting coffee shops in Makassar City have become part of the lifestyle and fashion of various groups as a place of work and business. , as a literacy space, and as a means of entertainment.